Performance analysis of ERS using R134a - An experimental investigation (Part 1) – Ejector design and performance analysis. Issue 1 (March 2021) - Kumar, Vikas; Tiwari, Sandeep; Sachdeva, Gulshan; Jain, Vaibhav; Mittal, Vishal; Sharma, Paras; Rajput, Vipin; Bhardwaj, Homenidhi
Abstract: The present study proposed a mathematical model for calculating the entrainment ratio and area-ratio for the single-phase ejector working double choking conditions. The model contains gas dynamic equations and is used to calculate performance of ejector for R134a and R141b refrigerants. The model is also validated with the experimental results of the previous researcher and found results are in good coherence with average deviation of -0.287% and 2.48% for area-ratio and entrainment ratio respectively.